Implementation of perturb and observe method of maximum power point tracking in SIMSCAPE/MATLAB - Verma, Deepak; Nema, Savita; Nema, R. K. (2017 International Conference on Intelligent Sustainable Systems (ICISS), 2017)
With the increased awareness for environmental preservation and the drive to reduce greenhouse emissions, there has been significant shift towards renewable energy sources. Solar energy being clean and commercially competitive, have been one of the most popular choice. In this paper solar photovoltaic (SPV) technology along with the Perturb and Observe (P&O) method of maximum power point tracking (MPPT) is presented. The research objectives are formulated in context of the most popular MPPT technique that is P&O and its implementation is presented in this paper. Implementation is done using physical library given in MATLAB called SIMSCAPE.